Lack of Macrophage Migration Inhibitory Factor Reduces Susceptibility to Ventricular Arrhythmias During the Acute Phase of Myocardial Infarction - Lyu J; Huang J; Wu J; Yu T; Wei X; Lei Q (Dove Medical Press, 2021)
Juanjuan Lyu,1 Jia Huang,2,3 Jin Wu,1 Tao Yu,3,4 Xinchuan Wei,2,3 Qian Lei2,3 1Department of Pediatrics, West China Second University Hospital, Sichuan University, Chengdu, 610041, People’s Republic of China; 2Department of Anesthesiology, Sichuan Provincial People’s Hospital, University of Electronic Science and Technology of China, Chengdu, 610072, People’s Republic of China; 3Chinese Academy of Sciences Sichuan Translational Medicine Research Hospital, Chengdu, 610072, People’s Republic of China; 4Department of Cardiac Surgery, Sichuan Provincial People’s Hospital, University of Electronic Science and Technology of China, Chengdu, 610072, People’s Republic of ChinaCorrespondence: Qian Lei Email leiqianggh@163.comBackground: Macrophages are involved in inflammatory responses and play a crucial role in aggravating ventricular arrhythmias (VAs) after myocardial infarction (MI). Macrophage migration inhibitory factor (MIF) participates in inflammatory responses during acute MI. In the present study, we hypothesized that knockout (KO) of MIF may prevent VAs during the acute phase of MI by inhibiting macrophage-derived pro-inflammatory mediators.Methods and Results: We demonstrated that MIF-KO mice in a mouse model of MI exhibited a significant decrease in susceptibility to VAs both in vivo (84.6% vs 40.7%, P < 0.05) and ex vivo (86.7% vs 40.0%, P < 0.05) at day 3 after MI compared with that in wild-type (WT) mice. Both WT and MIF-KO mice presented similar left ventricular contractility, peri-infarct myocardial fibrosis and sympathetic reinnervation, and circulating and local norepinephrine levels during the acute phase of MI. Meanwhile, MIF-KO mice had inhibited macrophage aggregation, alleviated connexin 43 (Cx43) redistribution, and reduced level of pro-inflammatory mediators, including tumor necrosis factor-α and interleukin-1β (P < 0.05) at day 3 after MI. The differences in susceptibility to VAs, expression of pro-inflammatory mediators, and Cx43 redistribution after MI between WT and MIF-KO mice disappeared by macrophage depletion with clodronate liposomes in both groups. Furthermore, the pro-inflammatory activity of cultured peritoneal macrophages was inhibited by MIF deficiency and recovered with replenishment of exogenous MIF in vitro.Conclusion: In conclusion, we found that lack of MIF reduced the susceptibility to VAs in mouse heart during the acute phase of MI by inhibiting pro-inflammatory activity of macrophages and improving gap-junction and electrical remodeling.Keywords: myocardial infarction, ventricular arrhythmias, macrophage migration inhibitory factor, inflammatory mediators, sympathetic nerve